2017
DOI: 10.1186/s13068-017-0942-6
|View full text |Cite
|
Sign up to set email alerts
|

Oleaginous yeast Yarrowia lipolytica culture with synthetic and food waste-derived volatile fatty acids for lipid production

Abstract: BackgroundThe sustainability of microbial lipids production from traditional carbon sources, such as glucose or glycerol, is problematic given the high price of raw materials. Considerable efforts have been directed to minimize the cost and find new alternative carbon sources. Volatile fatty acids (VFAs) are especially attractive raw materials, because they can be produced from a variety of organic wastes fermentation. Therefore, the use of volatile fatty acids as carbon sources seems to be a feasible strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
83
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 42 publications
9
83
0
2
Order By: Relevance
“…When VFAs are used as a carbon source, the inhibitory effect of high acid concentration (up to 5 g/L) on yeast growth is well known (Fei et al, ; Fontanille et al, ; Huang et al, ; Liu, Yuan, Liu, & Huang, ). In this sense, several studies have concluded that the toxic effect on yeast increases with increasing VFA chain length (Gao et al, ; Liu, Yuan, Liu, & Huang, ). However, J. Liu et al () reported higher biomass and lipid yields (1.6 and 0.4 g/g C, respectively) from 5 g/L of butyric acid than from acetic or propionic acids in C. curvatus .…”
Section: Oleaginous Microorganisms For Oil Productionmentioning
confidence: 98%
See 2 more Smart Citations
“…When VFAs are used as a carbon source, the inhibitory effect of high acid concentration (up to 5 g/L) on yeast growth is well known (Fei et al, ; Fontanille et al, ; Huang et al, ; Liu, Yuan, Liu, & Huang, ). In this sense, several studies have concluded that the toxic effect on yeast increases with increasing VFA chain length (Gao et al, ; Liu, Yuan, Liu, & Huang, ). However, J. Liu et al () reported higher biomass and lipid yields (1.6 and 0.4 g/g C, respectively) from 5 g/L of butyric acid than from acetic or propionic acids in C. curvatus .…”
Section: Oleaginous Microorganisms For Oil Productionmentioning
confidence: 98%
“…Besides this, in the ex novo pathway, the microbial lipids produced contain lower quantities of TAGs and somehow higher quantities of FFAs as compared with lipid produced through de novo process (Papanikolaou & Aggelis, ). There are some examples related to the microorganism's growth with hydrophobic and hydrophilic materials as cosubstrates (Beopoulos et al, ; Fontanille, Kumar, Christophe, Nouaille, & Larroche, ; Gao, Li, Zhou, Cheng, & Zheng, ) indicating possible simultaneous ex novo and de novo lipid biosynthesis pathways.…”
Section: Oleaginous Microorganisms For Oil Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, there is a growing interest in using volatile FAs (VFAs) as carbon sources for lipid production (Beopoulos et al, ; Fei et al, ; Qiao et al, ). VFAs can be obtained from agro‐industrial waste and several types of biodegradable organic waste (Papanikolaou, Galiotou‐Panayotou, Fakas, Komaitis, & Aggelis, ); in theory, they should have higher conversion efficiencies than sugar‐based carbon sources because of the shorter metabolic pathways involved (Gao, Li, Zhou, Cheng, & Zheng, ).…”
Section: Introductionmentioning
confidence: 99%
“…Propionate, one of the most common VFAs, can be used by Yarrowia lipolytica as its sole carbon source in lipid production (Fontanille, Kumar, Christophe, Nouaille, & Larroche, ; Kolouchová, Schreiberová, Sigler, Masák, & Řezanka, ; Gao et al, ). Recently, Y .…”
Section: Introductionmentioning
confidence: 99%